The Role of Deep Geofluids in the Enrichment of Sedimentary Organic Matter: A Case Study of the Late Ordovician-Early Silurian in the Upper Yangtze Region and Early Cambrian in the Lower Yangtze Region, South China. (18th December 2020) - Zhang, Kun; Peng, Jun; Liu, Weiwei; Li, Bin; Xia, Qingsong; Cheng, Sihong; Yang, Yiming; Zeng, Yao; Wen, Ming; Liu, Dongmei; Huang, Yizhou; Zhong, Li; et al.
Abstract : Organic matter is the material basis for shales to generate hydrocarbon, as well as the main reservoir space and seepage channel for shale gas. When the thermal evolution degree is consistent, the organic carbon content in present shales is subject to the abundance of primitive sedimentary organic matter. Deep geofluids significantly influence the sedimentary organic matter's enrichment, but the mechanism remains unclear. This paper is aimed at determining how hydrothermal and volcanic activities affected the enrichment of sedimentary organic matter by studying lower Cambrian shales in the lower Yangtze region and upper Ordovician-lower Silurian shales. Oxidation-reduction and biological productivity are used as indicators in the study. The result shows that hydrothermal or volcanic activities affected the enrichment of sedimentary organic matter by influencing climate changes and the nutrients' sources on the waterbody's surface and reducing water at the bottom. In the lower Cambrian shales of the Wangyinpu Formation in the lower Yangtze region, hydrothermal origin caused excess silicon. During the sedimentary period of the lower and middle-upper Wangyinpu Formation, vigorous hydrothermal activities increased the biological productivity on the waterbody's surface and intensified the reducibility at the bottom of the waterbody, which enabled the rich sedimentary organic matter to be well preserved. During the sedimentary period of the lower upper Ordovician Wufeng Formation and the lower Silurian Longmaxi Formation in the upper Yangtze region, frequent volcanic activities caused high biological productivity on the waterbody surface and strong reducibility at the bottom of the waterbody. As a result, the abundant organic matter deposited from the water surface can be well preserved. During the sedimentary period of the upper Longmaxi Formation, volcanic activities died down gradually then disappeared, causing the biological productivity on the water surface to decrease. Besides, the small amount of organic matter deposited from the water surface was destroyed due to oxidation.